Accuracy of Guided Implant Surgery in 25 Edentulous Arches: A Laboratory Observational Study. Issue 8 (7th August 2020) - Ben Yehuda, Daniel; Weber, Hans‐Peter; Finkelman, Matthew; Sicilia, Elena; Muftu, Ali; Chochlidakis, Konstantinos; Papaspyridakos, Panos
Abstract: Purpose: To assess the accuracy of template‐guided implant surgery for edentulous arches. Materials and Methods: The stone master casts of 25 edentulous arches treated with either 4 or 6 implants with CBCT generated template‐guided surgery were included in this observational cohort study. The stone casts generated from the surgical templates (group one) prior to implant placement were digitized into Standard Tesselation (STL) files with a reference scanner. For comparison, the stone master casts derived from intraoral complete‐arch impressions after implant placement (group two) were also digitized. The resultant STL files were superimposed and best‐fit‐alignment algorithm was used to quantify the 3D deviations present between the two groups. Descriptive statistics were computed for all categorical variables. Due to the presence of nonindependent samples between maxillary and mandibular casts, a mixed‐effects model was used. Results: Deviations between the implant analogs of the stone casts representing digitally planned versus actually placed implants were found. The mean root‐mean‐square error (RMSE) between all 25 arches was found to be 0.2 mm (SD ± 0.15). The mean RMSE between presurgical and postsurgical maxillary stone casts were 0.19 ± 0.15 mm, while between mandibular stone casts were 0.21 ± 0.16 mm and were not significant ( p = 0.67). The mean RMSE between presurgical and postsurgical stone casts arches with 4 versus 6 implants were found to be significant ( p = 0.01). Conclusions: According to the results of the study and based on the amount of 3D deviations between the digitally planned implant positions and the actually placed implants, template‐guided surgery is a safe treatment modality for implant placement in edentulous arches.